2018
DOI: 10.1089/acm.2018.0048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soft Tissue Techniques on Headache Impact, Disability, and Quality of Life in Migraine Sufferers: A Pilot Study

Abstract: Soft tissue techniques based on MTrP therapy and stretching were helpful for improving certain aspects of migraine, such as the impact and disability caused by the headache, and the frequency and intensity of headache; however, when combined with suboccipital soft tissue inhibition, the treatment effect was larger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 33 publications
3
37
0
4
Order By: Relevance
“…These findings support previous studies that determined the myofascial release techniques as the best option to manage patients with migraine headache. [ 6 11 ] In line with the current study, Espí-López et al . [ 12 ] found that the suboccipital soft-tissue inhibition caused significant improvement of headache frequency, disability, and increased CROM in the tension-type patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings support previous studies that determined the myofascial release techniques as the best option to manage patients with migraine headache. [ 6 11 ] In line with the current study, Espí-López et al . [ 12 ] found that the suboccipital soft-tissue inhibition caused significant improvement of headache frequency, disability, and increased CROM in the tension-type patients.…”
Section: Discussionsupporting
confidence: 90%
“…For stretching of the SCM muscle, the therapist performed contralateral lateral flexion and ipsilateral rotation of the head to achieve stretching, separating the origin, and the insertion of the SCM muscle. [ 6 ]…”
Section: Methodsmentioning
confidence: 99%
“…La zona cervical y torácica de los pacientes con migraña presentan disfunciones músculo-esqueléticas (Luedtke, Starke, y May, 2018), lo cual está relacionado con la activación del sistema trigeminal y los síntomas de la migraña (Ferracini et al, 2017). Por tanto, la TM, incluyendo manipulación o movilización articular espinal, intervenciones de tejido blando, ejercicio terapéutico y terapias con punción, ha sido estudiada en pacientes con cefaleas primarias, y ofrecen posibles efectos positivos (Bevilaqua-Grossi et al, 2016;Calixtre et al, 2018;Cerritelli et al, 2015;Dunning et al, 2016;Espí-López et al, 2018;Fernández-de-Las-Peñas y Cuadrado, 2016;Garrigós-Pedrón et al, 2018;Garrigós-Pedrón et al, 2018;Tuchin, Pollard, y Bonello, 2000;Voigt et al, 2011).…”
Section: Eficacia De La Terapia Manual Articulatoria Vertebral En Pacientes Con Migrañaunclassified
“…15 No studies were identified evaluating the effect of physiotherapy including mobilization and/or specific exercises. Studies published after the cutoff date of the systematic review have shown that physiotherapy interventions such as myofascial treatments 16,17 or a combination of manual therapy and exercises 18 also seem to be effective for migraine. Aerobic endurance training has also been reinvestigated in recent trials 19,20 reporting an effectiveness for migraine frequency reduction.…”
Section: Introductionmentioning
confidence: 99%